2020
DOI: 10.3390/cancers12020514
|View full text |Cite
|
Sign up to set email alerts
|

How to Classify Pituitary Neuroendocrine Tumors (PitNET)s in 2020

Abstract: Adenohypophyseal tumors, which were recently renamed pituitary neuroendocrine tumors (PitNET), are mostly benign, but may present various behaviors: invasive, “aggressive” and malignant with metastases. They are classified into seven morphofunctional types and three lineages: lactotroph, somatotroph and thyrotroph (PIT1 lineage), corticotroph (TPIT lineage) or gonadotroph (SF1 lineage), null cell or immunonegative tumor and plurihormonal tumors. The WHO 2017 classification suggested that subtypes, such as male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(143 citation statements)
references
References 93 publications
4
104
0
10
Order By: Relevance
“…Therefore, the higher expression of E2F, MYC, and miR-17-5p in invasive and proliferative tumours (grade 3) than in grade 1 (non-invasive tumours) confirms that both invasiveness and proliferation must be taken into account in PitNET classification [20]. In addition, the high expression of these genes and miRNA, implicated in the cancer, confirms that an invasive and proliferative tumour is not a benign adenoma as a non-invasive tumour, with or without proliferation [20].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Therefore, the higher expression of E2F, MYC, and miR-17-5p in invasive and proliferative tumours (grade 3) than in grade 1 (non-invasive tumours) confirms that both invasiveness and proliferation must be taken into account in PitNET classification [20]. In addition, the high expression of these genes and miRNA, implicated in the cancer, confirms that an invasive and proliferative tumour is not a benign adenoma as a non-invasive tumour, with or without proliferation [20].…”
Section: Discussionmentioning
confidence: 66%
“…However, many researchers have raised doubts about their usefulness [12,[23][24][25]. Indeed, some years ago, Trouillas et al [19,20] suggested a classification of the behaviour of pituitary tumours taking into account not only markers of proliferation, but also the IHC type, the invasiveness of the tumours, and their ability to relapse. To the best of our knowledge, E2F1 and MYC have never been studied as possible biomarkers of PitNETs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2017 WHO classi cation classi es PitNETs into seven morphofunctional types and three lineages. The French ve-tiered classi cation emphasizes tumor proliferation and invasion, which provide prognostic value for the clinical treatment of PitNETs [5]. Mario et al found gonadotroph signatures in some corticotroph and somatotroph PitNETs by integrated pangenomic analyses [4].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these considerations prompted a multidisciplinary group of experts in pituitary pathology to propose the new terminology "pituitary neuroendocrine tumor (PitNET)" instead of "pituitary adenoma" (Table 1) [23]. Thus, all anterior pituitary tumors are considered as lesions showing a potential clinical impact that can be additionally evaluated and better defined in terms of prognosis using a multiparametric approach including the Ki67 proliferative index and radiology appearance (Table 2) [24,25]. Although this new approach appears appropriate and clinically useful since it reflects the real biology of these tumors, it is still matter of debate [26][27][28].…”
Section: Pituitary Glandmentioning
confidence: 99%